Memorias del desaliento. Acercamiento a dos cuentos cubanos contemporáneos: “Huracán” de Ena Lucía Portela y “La yerba atrae a los tiburones” de Michel Perdomo - Caamaño, Virginia (2012)
This study addresses two contemporary Cuban short stories, about specific moments in the lives of the protagonists, who express their disenchantment in regards to their country´s precarious condition and political situation. They show their rejection towards the Revolution, whose principles they grew up under. The effects of globalization and its appropriation by islanders allows the reader to appreciate the media´s reach in terms of the adoption of foreign ideas and consumer habits, manifested in the protagonists´ attempts to emigrate to the idealized United States, from a society that appears to be closed off to the exterior. The characters´ failed dreams lead in most cases to an imaginary evasiveness, marked by disencouragement.